Mass differences of light hadron isomultiplets - Palladino, B. E. [UNESP]; Ferreira, P. Leal [UNESP] (American Physical Society (APS), 1989)
Mass differences of low-lying, nonstrange, hadron isomultiplets are investigated in the framework of a relativistic, independent quark potential model, implemented by center-of-mass, one-gluon-exchange, and pion-cloud corrections. The introduction of pionic self-energy corrections with non-degenerate intermediate states is instrumental in our analysis, playing also a fundamental role for a successful description of the - mass splitting. The effect of the superposition of all these corrections is discussed in some detail for the p-n, +-0, +-0, and ++-0 mass differences. The corresponding hadronic masses are also calculated with suitable values for the hadronic sizes and quark masses. © 1989 The American Physical Society.